2022
DOI: 10.1177/20584601221096680
|View full text |Cite
|
Sign up to set email alerts
|

Systemic air embolism following computed-tomography-guided transthoracic needle biopsy of lung lesion – a systematic search of case reports and case series

Abstract: Background Systemic air embolism is a rare, however potentially fatal, low incidence, complication to CT-guided transthoracic needle biopsy of lung lesions. Purpose The purpose of this review of case reports and series was to pool data about this rare complication and glance for a pattern or similarities in the patients’ initial symptoms and course, as well as the management of the patients in relation to current guidelines. Material and methods PubMed was searched for case reports and case series about system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…Subsequently, the patient was placed in the Trendelenburg position. Previous research has shown that the Trendelenburg position has no significant effect on preventing bubbles in arteries from reaching the brain [ [14] , [15] , [16] ]; however, many physicians still place the patient in this position empirically in clinical practice [ [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] ], and a recent analysis seems to indicate a good prognosis of patients in the Trendelenburg position in the treatment of symptomatic air embolism. This approach is controversial but still worth considering; complications, including airway edema and cerebral edema, need to be controlled [ 3 , 4 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the patient was placed in the Trendelenburg position. Previous research has shown that the Trendelenburg position has no significant effect on preventing bubbles in arteries from reaching the brain [ [14] , [15] , [16] ]; however, many physicians still place the patient in this position empirically in clinical practice [ [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] ], and a recent analysis seems to indicate a good prognosis of patients in the Trendelenburg position in the treatment of symptomatic air embolism. This approach is controversial but still worth considering; complications, including airway edema and cerebral edema, need to be controlled [ 3 , 4 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…38 Pietersen et al's review of air embolism complicating lung biopsy had 15.5% mortality, the majority of which were due to cardiac arrest. 17 However, 63% had no sequela and 9% had only minor sequela. Besseraeu et al reported outcomes in 119 patients with air embolism treated with HBO.…”
Section: Prognosismentioning
confidence: 97%
“…15,16 In Pietersen's literature review, air was mostly found in the aorta or left heart (>50% of cases) with the coronary arteries (34%) and cerebral arteries (30%) less commonly affected. 17 Performing the biopsy with suspended respiration and occluding the hub with a finger or a few drops of saline to create a water seal are unverified techniques which may minimize the likelihood of air embolus.…”
Section: Etiologymentioning
confidence: 99%
See 2 more Smart Citations